Pincer nails: an initial and isolated cutaneous manifestation of systemic lupus erythematosus - Manoj Karbhari Pawar (Termedia Publishing House, 2017)
Introduction . Pincer nail deformity due to systemic lupus erythematosus is a rare phenomenon and only three cases have been reported to date. Objective . To present a case of pincer nails in a systemic lupus erythematosus patient and a brief review of the literature. Case report . A 15-year-old girl presented with multiple painful pincer nail deformities, fever and joint pain of 6 months duration. On evaluation and laboratory investigations the patient fulfilled the criteria for systemic lupus erythematosus. Systemic treatment with glucocorticosteroids and antimalarials led to resolution of fever and joint pain but nail deformities did not improve. Conclusions. Pincer nail may be an early and important sign of systemic lupus erythematosus in certain patients.